Cytology of mixed germ cell tumor with mediastinal metastasis - Dagli, Adile Ferda; Pehlivan, Sultan; Cihangiroglu, Guelcin; Ozercan, Mehmet Resat (Wolters Kluwer Medknow Publications, 2009)
Nonseminomatous germ cell tumors of the testis are common and are very aggressive malignant tumors. Most of the cases have metastases at the time of diagnosis, and involvement of the posterior mediastinum in particular is well known. A 33 year-old male patient presented with complaints of a swelling on the right side of the neck that had been growing for the last month, as well as shortness of breath and cough. His thoracic computed tomography (CT) showed a 1.5 cm lymph node on the anterior mediastinum and a mass of about 11 x 10 x 8 cm extending from the right lung apex to the right hilus, with regular contours and without contrast enhancement. The patient, who was given the preliminary diagnosis of a mixture metastatic bronchial tumor plus lymphoma, was subjected to transthoracic fine needle aspiration cytology (FNAC). His abdominal CT revealed a hypodense, heterogeneous and cystic necrotic mass of about 10 x 7 x 5 cm that was para-aortic at the infrarenal level (initially predicted as a lymphoma). The patient, who could not be typed in his cytopathological examination, was diagnosed with malignant epithelial tumor and was recommended to undergo a genitourinary system examination. Upon finding a high alpha fetoprotein (AFP) value, a scrotal ultra sonography was performed which showed a mass filling the right testis. Histopathological examination of the orchiectomy material resulted in the diagnosis of mixed germ cell tumor (60% mature teratoma and 40% yolk sac tumor). Even though metastatic lesions are mostly seen in the posterior mediastinum, our findings reveal that specimens obtained with FNAC from the anterior mediastinum bear discohesive, pleomorphic, small nuclei in epithelial cells with microvacoules in the cytoplasm. These cytopathological alterations in specimens from the anterior mediastinum might promote germ cell and yolk sac tumors.
Keywords: Nonseminomatous germ cell tumor; testis; mixed germ cell tumor; fine needle aspiration cytology